UAV-BASED PHOTOGRAMMETRY DATA TRANSFORMATION AS A BUILDING INSPECTION TOOL: APPLICABILITY IN MID-HIGH-RISE BUILDING - Jati, Didit Gunawan Prasetyo (Jurnal Teknik Sipil, 2021)
The photogrammetric concept is used as a practical implementation of this study. Data management is proposed as an active contribution in the process of data integration and data in-operability to develop solutions based on UAV-based Photogrammetry as part of building inspection activities. Point Cloud adjusts the main role as data to initialize objects whose information can be represented in 2D / 3D / 4D rich-data format. Decision making on each management framework is planned with the DJI Go and Pix4D Capture Application which is controlled by a smartphone that has been pre-configured for the plan UAV flights. The flight plan quality control, flight mission supervision, and data acquisition results are important factors in the management and related infor-mation framework. The Point Cloud created by the SfM (Structure from Motion) application is then imported by Autodesk Recap and reconstructed in Revit BIM. The 3D Point Cloud is lastly enhanced with some practically detailed information to contribute to the data management experiment. The collaboration model of this study is presented using AR / VR (Augmented Reality / Virtual Reality) to enable mobile monitoring as a research objective and substantial examination. The essence of this study is to develop UAV-based Photogrammetry / BIM / AR-VR as a method to reduce the risk of data mismatches, monitor communications, and increase the impact of practical instructions on de-cision making on building inspection activities. The results of each verified workflow show that the methodology applied produces informational and visual data products that allow user mobility within the scope of building inspection and monitoring. Furthermore, device limitations do not affect the data acquisition process to provide user safety and efficiency.